PENGARUH PENGAWASAN DAN KOMITMEN TERHADAP KEDISIPLINAN KARYAWAN PADA TOSERBA BELIMBING INDAH DI PURBOLINGGO KABUPATEN LAMPUNG TIMUR - Joko Siswanto; Hikmatul Aliyah (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2018)
Employee Discipline is one of the spearheads of the company that gets the maximum profit through marketing activities. Supervision and Commitment are ways to improve Employee Discipline. This study aims to 1. Determine whether there is Supervision of Employee Discipline in Belimbing Indah Purbolinggo Department Store East Lampung District 2. Know whether there is a Commitment to Employee Discipline in Indah Purbolinggo Belimbing Department Store in East Lampung Regency 3. Know what is recommended Supervision and Commitment to Discipline Employees At Indah Belimbing Department Store Purbolinggo, East Lampung Regency. This research was conducted with the independent variable Supervision and Commitment as well as variables conducted by Employee Discipline. Data analysis techniques using Simple Linear Regression with a regression equation: Y '= a + b1X1 + b2X2 + ... + bn Xn. After the data is obtained, the following regression is obtained: Y = 11,081 + 0.415 X1 + 0.330X2. The coefficient of determination in this study is 74.5% the dependent variable is supported by the independent variable and 25.5 is requested by other variables. While the F-count is 6.790 greater than the F-table of 2.063 with a significance level of 5%. To find out which independent variable is more important, it is seen from the equation Y = 11,081 + 0.415 X1 + 0.330X2. it turns out 0.415 0.330, this means that supervision is more dominant than commitment to employee discipline. From the results of the analysis, the proposed working hypothesis can be substantiated.